Bottom Contact Engineering for Ambient Fabrication of >25% Durable Perovskite Solar Cells - Yuan, Ligang; Zou, Shibing; Zhang, Kaicheng; Huang, Peng; Dong, Yuyan; Wang, Jiarong; Fan, Kezhou; Lam, Man Yu; Wu, Xiao; Cheng, Wei; Tang, Ruijia; Chen, Wenhao; et al. (Advanced Materials, 2024)
The bottom contact in perovskite solar cells (PSCs) is easy to cause deep trap states and severe instability issues, especially under maximum power point tracking (MPPT). In this study, sodium gluconate (SG) is employed to disperse tin oxide (SnO2) nanoparticles (NPs) and regulate the interface contact at the buried interface. The SG-SnO2 electron transfer layer (ETL) enabled the deposition of pinhole-free perovskite films in ambient air and improved interface contact by bridging effect. SG-SnO2 PSCs achieved an impressive power conversion efficiency (PCE) of 25.34% (certified as 25.17%) with a high open-circuit voltage (VOC) exceeding 1.19 V. The VOC loss is less than 0.34 V relative to the 1.53 eV bandgap, and the fill factor (FF) loss is only 2.02% due to the improved contact. The SG-SnO2 PSCs retained around 90% of their initial PCEs after 1000 h operation (T90 = 1000 h), higher than T80 = 1000 h for the control SnO2 PSC. Microstructure analysis revealed that light-induced degradation primarily occurred at the buried holes and grain boundaries and highlighted the importance of bottom-contact engineering.
CRIS-Team Scopus Importer:2024-08-09
Keywords: bottom contact; perovskite solar cell; photodegradation; SnO; sodium gluconate